Intubation in burns patients: a 5-year review of the Manchester regional burns centre experience. Issue 3 (May 2021) - Dingle, L.A.; Wain, R.A.J.; Bishop, S.; Soueid, A.; Sheikh, Z.
Highlights: Majority of patients are intubated appropriately according to published criteria. Up to 30% of intubated burn patients are extubated within 48 h. Intubation/ventilation-related complications in 37.5% of intubated burn patients. Abstract: Despite criteria to guide intubation from the American Burn Association (ABA), concerns remain regarding over-intubation of burns patients. The purpose of this study was to review appropriateness of intubation at a UK regional burns centre over a 5-year period. A 5-year retrospective review of adult patients admitted to the Manchester Burns Centre who underwent intubation at or prior to admission was performed. Intubations for non-burn indications or burns >40%TBSA were excluded. Patient demographic and burn characteristics data were extracted from medical records. Indications for intubation were compared to ABA and Denver criteria. 47 patients were identified, of which 40 met inclusion criteria for analysis. 72.5% and 95% of these patients met ABA or Denver criteria respectively. 30.8% of patients were extubated within 48 h. 50% patients extubated within 48 h had ≤1 indication for intubation or negative laryngoscopy. Complications related to intubation and ventilation were noted in 37.5% of patients, with ventilation associated pneumonia (VAP) being the most common occurring in 27.5%. 95% of patients fulfilled recognised criteria for intubation. However, 30% were extubated within 48 h, suggesting potentially avoidable intubation. This study suggests current intubation criteria may over-estimate risk of airway compromise and supports results from non-UK studies that a proportion of patients may be suitable for close observation rather than early intubation.